2012
DOI: 10.1515/jag-2011-0006
|View full text |Cite
|
Sign up to set email alerts
|

GNSS precise point positioning in regional reference frames using real-time broadcast corrections

Abstract: Abstract. As a result of the Real-Time IGS Pilot Project (RT-IGS) and the EUREF Real-Time Analysis Project (EUREF-RT), real-time GNSS satellite orbit and clock corrections to broadcast ephemeris, the so-called real-time broadcast corrections (BC), have become available for the application in precise point positioning (PPP). The realtime BCs are currently available in global as well as in regional reference frames. In this contribution the PPP usage and performances of these global and regional BCs are analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…To shorten the stated time-span, Teunissen et al (1997) introduced the principle of phase-only ambiguity resolution. Recent contributions have demonstrated that relatively fast phase-only ambiguity-resolved positioning (∼10-30 s) is indeed feasible (Huisman et al 2010, Wang et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…To shorten the stated time-span, Teunissen et al (1997) introduced the principle of phase-only ambiguity resolution. Recent contributions have demonstrated that relatively fast phase-only ambiguity-resolved positioning (∼10-30 s) is indeed feasible (Huisman et al 2010, Wang et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…However, to reach such an accuracy, long convergence time from tens of minutes to hours can be required (Banville et al 2014;Leandro et al 2011;Yu and Gao 2017). For single-frequency users, the precision of the kinematic PPP results by also applying external ionospheric information is normally at decimeter level (Huisman et al 2012; van Bree and Tiberius 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The PPP solution convergence time ranges from several minutes to a few hours depending on both the expected position accuracy and the mode of receiver operation. The convergence time can significantly be reduced by fixing the carrier phase ambiguities [ 11 , 12 , 13 ]. This, however, requires additional correction products on signals delays, for instance the corrections of uncalibrated phase delays (UPD) [ 14 ], which are currently difficult to obtain real-time.…”
Section: Introductionmentioning
confidence: 99%